The Emerging Gaming Sector in Zimbabwe: Obstacles and Opportunities for Revenue Generation - Ngoma, Permanent; Moyo, Gorden; Gororo, Gloria; Nhliziyo, Mbongeni (Archives of Business Research, 2025)
This article discusses gaming as a potential financing mechanism. It explores the opportunities presented by the emerging gaming sector in addressing Zimbabwe’s development financing woes. The rise of the gaming industry is a global phenomenon propelled by the Fourth Industrial Revolution (4IR) and Artificial Intelligence (AI) both of which define the current period as a Digital Era. This digital era is characterized by technological developments such as Internet of Things, nanotechnologies, robotics, biotechnologies, blockchain technologies, 5 generation technologies, autonomous vehicles, AI and numerous others. In this new and still emerging age, daily life including work, business, shopping, learning, and leisure, has become inextricably linked to digital technologies. What is more relevant for the present analysis is the increasing penetration of mobile devices, expanding internet connectivity, and rising access to digital platforms. The article also explores several obstacles including regulatory constraints, lack of investor awareness, and inadequate technological infrastructure as major barriers to the growth of the gaming industry in Zimbabwe. Besides exploring the obstacles and opportunities, the article also proposes various ways that can be deployed in order to scale-out and scale-up the gaming industry in Zimbabwe. The proposed measures could possibly position the country as a competitive player in the regional and global gaming market.